Probability-Based Validation of the Forensic Method "Microscopic Analysis of Textile Fibers" - S. A. Smirnova; G. I. Bebeshko; I. P. Lyubetskaya; G. G. Omel’yanyuk; A. I. Usov (Теория и практика судебной экспертизы, 2019)
The results of validation of the method “Microscopic analysis of textile fibers” used in forensic fiber examination are presented. An attempt is made to estimate reliability of testing of this method numerically by the proportions of right and false results and credibility ratio.The testing method under consideration consists in establishing a set of external characteristics of natural and chemical textile fibers: color, peculiarities of coloration, morphological features, presence/absence of a matting agent. These generic characteristics are used in forensic textile analysis. As the objects of testing fiber samples from comparative collection of a forensic fiber laboratory were used. Four experts participated in the experiment independently examining eleven fiber samples by eleven external characteristics for a week.A low (2,2 %) rate of false results in relation to the total number of tests was established as well as the low (less than 3,0 %) rate of each expert’s false results. The probability of the right results of characteristics’ assessment is 30 times higher than the probability of false results.The results of the experiment permit the conclusion that the method is suitable to be used in forensic fiber examination when dealing with various tasks: classification, identification, situational and diagnostic.